Orquestra de violões de Corrente-PI : um estudo de caso sobre o ensino coletivo no ambiente escolar - Silva, Dieudes Laenio de Sousa (2023)
This work aimed to understand and analyze the implications of group guitar teaching in the learning process in a School Orchestra. The empirical field of the research was a Guitar Orchestra, with an extended view to group guitar classes, developed at the Federal Institute of Piau í , more specifically at Campus Corrente. Regarding the methodological approach, the qualitative research guided the pedagogical experiences and the operationalization of the research during the work with the Orchestra, emphasizing the subjective aspects rel ated to human behavior and social phenomena through the Case Study. The research data were collected through observations and carrying out a work plan, recorded in a field note. The foundation and/or theoretical framework of the research was presented from two perspectives, the first that enabled the understanding of the methodology that led to the realization of activities with the orchestra, based on authors that led to the understanding of the pedagogical bases that underpin the group teaching of guitar and, to understand the data and the musical development from the worked step s, I took as a basis the concept of cooperative learning conceived from the reflections of Johnson, Johnson and Holubec (1999).